PDBe: improved findability of macromolecular structure data in the PDB. Issue Volume 48:Issue D1(2020) (6th November 2019) - Armstrong, David R; Berrisford, John M; Conroy, Matthew J; Gutmanas, Aleksandras; Anyango, Stephen; Choudhary, Preeti; Clark, Alice R; Dana, Jose M; Deshpande, Mandar; Dunlop, Roisin; Gane, Paul; Gáborová, Romana; et al.
Abstract: The Protein Data Bank in Europe (PDBe), a founding member of the Worldwide Protein Data Bank (wwPDB), actively participates in the deposition, curation, validation, archiving and dissemination of macromolecular structure data. PDBe supports diverse research communities in their use of macromolecular structures by enriching the PDB data and by providing advanced tools and services for effective data access, visualization and analysis. This paper details the enrichment of data at PDBe, including mapping of RNA structures to Rfam, and identification of molecules that act as cofactors. PDBe has developed an advanced search facility with ∼100 data categories and sequence searches. New features have been included in the LiteMol viewer at PDBe, with updated visualization of carbohydrates and nucleic acids. Small molecules are now mapped more extensively to external databases and their visual representation has been enhanced. These advances help users to more easily find and interpret macromolecular structure data in order to solve scientific problems.